2016
DOI: 10.1093/infdis/jiw535
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-36α attenuates sepsis by enhancing antibacterial functions of macrophages

Abstract: Our results demonstrate that IL-36α plays an important role in the host defense response to sepsis and suggest a potential therapeutic role for IL-36α in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Because phagocytes are important for bacterial clearance during sepsis [4, 11, 12], we investigated whether macrophage and/or neutrophil might mediate the beneficial effect of flagellin on sepsis. We first evaluated the importance of macrophages and neutrophils in the survival and bacterial clearance of flagellin-treated septic mice using cell depletion in a sublethal model of sepsis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because phagocytes are important for bacterial clearance during sepsis [4, 11, 12], we investigated whether macrophage and/or neutrophil might mediate the beneficial effect of flagellin on sepsis. We first evaluated the importance of macrophages and neutrophils in the survival and bacterial clearance of flagellin-treated septic mice using cell depletion in a sublethal model of sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogen-free 6–8-week-old female C57BL/6 mice were obtained from and raised at Chongqing Medical University. Polymicrobial sepsis was provoked by CLP as described in our previous studies [11, 12]. C57BL/6 mice were anesthetized with a mixture of xylazine (4.5 mg/kg) and ketamine (90 mg/kg) intraperitoneally (i.p.).…”
Section: Methodsmentioning
confidence: 99%
“…Pretreatment of macrophages with IL-36a enhances the ability of these cells to phagocytose and destroy Escherichia coli in vitro, which might explain how IL-36a provides protection against the outcome of sepsis induced by cecal ligation and puncture (91). In addition, the presence of IL-1RL2 on B cells (104) and the ability of IL-1RL2 to activate M2 macrophages (95) have been reported; however, the biological importance of these observations has not been examined.…”
Section: Function In Leukocyte Activationmentioning
confidence: 99%
“…Further studies demonstrated that the PKCδ‐TAT peptide inhibitor itself was not cytotoxic and had no bactericidal effects when added directly to cultures of Escherichia Coli or Salmonella Thyphirium in vitro suggesting that PKCδ inhibition may impact immune cell anti‐infective function either directly by impacting phagocyte function or indirectly by altering the environmental milieu. Impaired innate immune cell function has been associated with increased mortality in sepsis …”
Section: Discussionmentioning
confidence: 99%
“…Impaired innate immune cell function has been associated with increased mortality in sepsis. 46 To address this question, we examined immune cell recruitment to the peritoneal cavity and phagocytic capabilities of peritoneal macrophages. As phagocytic cell recruitment to the site of infection is the first line of defense, we examined the impact of PKCδ inhibition on recruitment of neutrophils and monocyte/macrophages.…”
Section: Discussionmentioning
confidence: 99%